A meta-analysis of the distribution, sources and health risks of arsenic-contaminated groundwater in Pakistan. (November 2018) - Shahid, Muhammad; Niazi, Nabeel Khan; Dumat, Camille; Naidu, Ravi; Khalid, Sana; Rahman, Mohammad Mahmudur; Bibi, Irshad
Abstract: Globally, millions of people who rely on groundwater for potable purposes and agriculture have been inadvertently exposed to toxic arsenic (As) because of its natural occurrence in groundwater in several countries of Asia, Europe and America. While the presence of As in groundwater and its impacts on human health have been documented in many countries, there is little information on As contamination in Pakistan. This review highlights, for the first time, the extent and severity of As-induced problems in Pakistan based on relevant published papers; discusses possible sources of As contamination of aquifers; and estimates As-induced potential health hazards in the country in relation to global data. Data from 43 studies (>9882 groundwater samples) were used to describe As variability in groundwater of Pakistan and for comparison with global data. The mean groundwater As content reported in these studies was 120 μg/L (range: 0.1–2090 μg/L; SD: ±307). About 73% of the values for mean As contents in the 43 studies were higher than the World Health Organization (WHO) permissible limit (10 μg/L) for drinking water, while 41% were higher than the permissible limit of As in Pakistan (50 μg/L). It was observed that groundwater samples in some areas of Punjab and Sindh provinces contained high As concentrations which were almost equal to concentrations reported in the most contaminated areas of the world. We predicted that the mean values of ADD, HQ and CR were 4.4 μg kg −1 day −1 (range: 0–77 μg kg −1 day −1 ), 14.7 (range: 0–256) and 0.0029 (range: 0–0.0512), respectively, based on mean As concentrations reported in Pakistan. In addition, this article proposes some integrated sustainable solutions and future perspectives keeping in view the regional and global context, as well as the on-ground reality of the population drinking As-contaminated water, planning issues, awareness among civil society and role of the government bodies. Based on available data, it is predicted that almost 47 million people in Pakistan are residing in areas where more than 50% of groundwater wells contain As concentrations above the WHO recommended limit of As in drinking water. Graphical abstract: Image 1 Highlights: In Pakistan, arsenic (As) concentrations exceed above WHO safe limit (10 μg/L) in some areas. This is the first review critically analyzing published data on groundwater As in Pakistan. Total 43 studies (>9882 groundwater samples) were used to describe As spatial variability. Sustainable solutions and important perspectives are proposed in regional and global context. Over 47 million people are estimated to be at potential risk of As poisoning in Pakistan. Abstract : Capsule: This review describes arsenic contamination of groundwater and associated health risks in Pakistan considering proposed scientific solutions proposed at global and regional scales.